Biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material

By catalyzing the growth of carbon nanotubes on biomass-derived carbon-based materials, the carbon nanotube @ carbon microtube composite material with a hierarchical structure is solved, and the impedance mismatch and narrow absorption bandwidth of electromagnetic wave absorbing materials is achieved, achieving wide bandwidth and strong Absorbent and lightweight microwave absorption performance, with simple process and low cost.

CN119119958APending Publication Date: 2024-12-13HUAIBEI NORMAL UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411269017.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Currently, the electromagnetic wave absorbing materials in hollow hierarchical structures have insufficient impedance mismatch, narrow absorption bandwidth, and large filling amount, which is difficult to meet the needs of wide bandwidth, strong absorption, lightweight and thin thickness of wave absorbing materials.

Method used

Using biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material, the carbon nanotubes with melamine as carbon source is catalyzed by mixing biomass rods with cobalt chloride, and then using chemical vapor deposition method to catalyze the growth of carbon nanotubes with melamine as carbon sources at high temperatures to form a hierarchical structure. carbon nanotube @ carbon microtube composite material.

Benefits of technology

It effectively improves the magnetic loss and polarization loss of the material, improves the dielectric loss, impedance matching characteristics and attenuation characteristics, achieves a wide effective absorption bandwidth and strong absorption performance, and has a simple process and low cost, which is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119958A_ABST
    Figure CN119119958A_ABST
Patent Text Reader

Abstract

The invention discloses a biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material, and relates to the technical field of electromagnetic wave absorbing materials, and a preparation method comprises the following steps: 1, washing biomass cattail sticks with water and ethanol, and then putting the washed biomass cattail sticks into a drying oven for drying; 2, mixing the biomass cattail sticks and cobalt chloride in an ethanol solution to obtain biomass cattail sticks adsorbed with Co < 2 + >; and 3, carrying out high-temperature calcination on melamine as a carbon source and the biomass cattail sticks adsorbed with Co < 2 + > in a nitrogen atmosphere by using a chemical vapor deposition method, and carrying out catalytic growth of carbon nanotubes on the biomass-derived carbon microtubes to finally obtain the carbon nanotube-carbon microtube composite material with a hierarchical structure. Therefore, according to the biomass derived carbon-based magnetic tubular composite electromagnetic wave absorbing material provided by the invention, the effective absorption bandwidth reaches 6.08 GHz under the conditions that the filling degree is 10wt% and the thickness is 1.8 mm, excellent microwave absorption performance is shown, and a new strategy is provided for efficient microwave absorption of a light magnetic carbon-based composite absorbent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of electromagnetic wave absorbing materials, and in particular to a biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material. Background Art

[0002] Electromagnetic radiation and interference have seriously affected information security, equipment performance and human health. In recent years, electromagnetic wave absorbing materials have attracted great attention from researchers and have achieved certain research results, such as carbon materials, graphene, carbon nanotubes (CNTs), magnetic materials, ceramic materials and MXene. For pure dielectric loss microwave absorbing materials, magnetic materials usually show poor electromagnetic loss capabilities at high temperatures due to the transition from ferromagnetism to paramagnetism and high density. Therefore, more research is focused on exploring new dielectric loss materials and studying potential mechanisms. However, how to promote the synergistic effect between magnetic and dielectric properties, improve attenuation performance and overcome the limitations of impedance matching, and then obtain excellent microwave absorption performance, has become a problem that carbon-based materials need to solve in the field of electromagnetic wave absorption.

[0003] A large number of studies have found that biomass-derived carbon materials have a natural hollow micron-tube structure, which makes them have high electrical conductivity and strong chemical stability, including advantages such as light weight, low cost, and sustainability. It is an effective way to meet the requirements of strong conductivity loss and polarization loss, special structure and good impedance matching characteristics, and has become an ideal candidate for high-performance microwave absorbers. However, the current hollow hierarchical structure electromagnetic wave absorbing materials still face the shortcomings of impedance mismatch, narrow absorption bandwidth, and large filling volume, which makes it difficult to meet the requirements of wide bandwidth, strong absorption, light weight, and thin thickness for absorbing materials. Summary of the invention

[0004] The purpose of the present application is to provide a biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material to solve the technical problem that the current hollow hierarchical structure electromagnetic wave absorbing materials have the disadvantages of impedance mismatch, narrow absorption bandwidth, large filling volume, etc., and it is difficult to meet the requirements of wide bandwidth, strong absorption, light weight, thin thickness, etc. for absorbing materials.

[0005] The present application discloses a biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material. The preparation steps of the biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material are as follows:

[0006] Step 1, washing the biomass cattail sticks with water and ethanol and then drying them in an oven to obtain washed biomass cattail sticks;

[0007] Step 2: Add the cleaned biomass cattail and cobalt chloride into the ethanol solution to obtain the biomass cattail with Co adsorbed thereon. 2+ of biomass cattail sticks;

[0008] Step 3: Using chemical vapor deposition, melamine is used as a carbon source and adsorbed with Co 2+ The biomass cattails are calcined at high temperature in a nitrogen atmosphere to catalytically grow carbon nanotubes on the biomass-derived carbon microtubes, and finally a biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material with a hierarchical structure is obtained.

[0009] Preferably, the specific steps of step 1 are: washing the biomass cattail sticks with water and ethanol for several times, and placing the washed cattail sticks in a 60° C. oven for continuous drying for 24 hours to obtain cleaned biomass cattail sticks.

[0010] Preferably, the specific steps of step 2 are: adding the cleaned biomass cattail sticks and cobalt chloride to the ethanol solution, ultrasonicating, heating and stirring; after the stirring, the mixture is allowed to stand and then taken out, and air-dried in a fume hood to obtain the biomass cattail sticks adsorbed with Co 2+ of biomass cattails.

[0011] Preferably, the specific steps of step 3 are: placing a melamine reagent and a container containing Co adsorbed thereon 2+ The containers of biomass cattails were placed in a horizontal tube furnace at N 2 The mixture was calcined for 2 h under a carbon atmosphere and naturally cooled to obtain a biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material with a hierarchical structure.

[0012] Preferably, in step 2, the mass ratio of biomass cattail sticks to cobalt chloride is 2:1 or 2:3, the volume of the ethanol solution is 20 ml, the ultrasonic time is 5 min, the heating and stirring temperature is 60°C, the time is 30 min, the standing time is 1 h, and the air-drying time is 24 h.

[0013] Preferably, during calcination in step 3, the temperature is raised to 800° C. at a heating rate of 5° C. / min.

[0014] Preferably, the melamine reagent and the Co adsorbed 2+ When the container of biomass cattails is placed in the horizontal tube furnace, the direction of the airflow is kept in the same direction as the melamine and Co adsorbed 2+ The front and rear placement directions of the biomass cattail sticks are consistent.

[0015] Therefore, the present application adopts the above-mentioned biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material, which has the following beneficial effects:

[0016] 1. Select biomass cattail sticks as the precursor of biomass carbon material; mix the biomass cattail sticks with cobalt chloride in an ethanol solution to obtain a carbon material adsorbed with Co 2+ biomass cattail; using chemical vapor deposition method, melamine was used as carbon source and adsorbed with Co 2+The biomass cattails are calcined at high temperature in a nitrogen atmosphere, and carbon nanotubes are catalytically grown on the biomass-derived carbon microtubes, and finally a composite material of carbon nanotubes @ carbon microtubes with a hierarchical structure is obtained. Specifically, the carbon-based electromagnetic wave absorbing material of the present invention is prepared by a simple one-step chemical vapor deposition strategy. Melamine is decomposed under high temperature conditions to provide a carbon source for the growing carbon nanotubes. Under the catalytic action of transition metal cobalt ions, carbon nanotube arrays grow on the surface of one-dimensional carbon microtubes, thereby obtaining a composite material of carbon nanotubes @ carbon microtubes with a hierarchical structure.

[0017] 2. The present invention effectively solves the problem of weak and single loss capacity of pure carbon materials, enhances the magnetic loss and polarization loss of the material, and effectively improves the dielectric loss, impedance matching characteristics and attenuation characteristics of the absorbing material.

[0018] 3. Compared with traditional electromagnetic wave absorbing materials, the present invention has the characteristics of wide effective absorption bandwidth and strong absorption intensity under the conditions of thin thickness and low filler loading, showing excellent microwave absorption performance;

[0019] 4. The present invention uses cattail as raw material, and the preparation method is simple, which not only has low material cost, but also can turn waste into treasure, improve resource utilization, and can be used for large-scale industrial production. The present invention provides a new strategy for achieving efficient microwave absorption of lightweight magnetic carbon-based composite absorbents. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 A flow chart of a method for preparing a biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material provided by the present invention;

[0021] Figure 2 This is a SEM image of the biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material prepared in Example 1 of the present invention;

[0022] Figure 3 This is the XRD pattern of the biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material prepared in Example 1 of the present invention;

[0023] Figure 4 This is a SEM image of the biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material prepared in Example 2 of the present invention;

[0024] Figure 5 This is the XRD pattern of the biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material prepared in Example 2 of the present invention;

[0025] Figure 6 This is a SEM image of the biomass-derived carbon material prepared in Comparative Example 1 of the present invention;

[0026] Figure 7This is the XRD pattern of the biomass-derived carbon material prepared in Comparative Example 1 of the present invention;

[0027] Figure 8 This is a reflection loss curve of the biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material prepared in Example 1 of the present invention with a filling degree of 10wt%;

[0028] Fig. 9 This is a reflection loss curve of the biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material prepared in Example 2 of the present invention with a filling degree of 10wt%;

[0029] Fig.10 This is a reflection loss curve of the biomass-derived carbon material prepared in Comparative Example 1 of the present invention with a filling degree of 10 wt%. DETAILED DESCRIPTION

[0030] Example 1

[0031] A method for preparing a biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material, such as Figure 1 The specific steps are:

[0032] Step 1: Prepare biomass cattail sticks

[0033] An appropriate amount of cattail biomass sticks were washed with water and ethanol for several times, and the washed cattail biomass sticks were placed in a 60° C. oven for continuous drying for 24 hours to obtain cleaned cattail biomass sticks.

[0034] Step 2: Mix the cleaned biomass cattail with cobalt chloride in an ethanol solution to obtain a biomass cattail with Co adsorbed thereon. 2+ of biomass cattail sticks;

[0035] Take 200 mg of the cleaned cattail biomass obtained in step 1 and 100 mg of cobalt chloride and add them to 20 ml of ethanol solution. After ultrasonication for 5 min, heat and stir at 60 ° C for 30 min. After stirring, let the mixture stand for 1 h, take it out, and air-dry it in a fume hood for 24 h to obtain the Co adsorbed 2+ of biomass cattails.

[0036] Step 3: using chemical vapor deposition method, melamine is used as carbon source and adsorbed with Co 2+ The biomass cattails are calcined at high temperature in a nitrogen atmosphere to catalytically grow carbon nanotubes on the biomass-derived carbon microtubes, and finally a biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material with a hierarchical structure is obtained.

[0037] The melamine reagent and the Co adsorbed 2+ The containers of biomass cattails were placed in the horizontal tube furnace according to the front and rear positions, and the airflow direction was kept in the same direction as the melamine and Co adsorbed2+ The front and back directions of the biomass cattail sticks are consistent. 2 The sample was calcined for 2 h at a heating rate of 5 °C / min to 800 °C in a molten-air atmosphere. After natural cooling, a biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material with a hierarchical structure was obtained, named Co-100.

[0038] Example 2

[0039] Step 1: Prepare biomass cattail sticks

[0040] An appropriate amount of cattail biomass sticks were washed with water and ethanol for several times, and the washed cattail biomass sticks were placed in a 60° C. oven for continuous drying for 24 hours to obtain cleaned cattail biomass sticks.

[0041] Step 2: Mix the cleaned biomass cattail with cobalt chloride in an ethanol solution to obtain a biomass cattail with Co adsorbed thereon. 2+ of biomass cattail sticks;

[0042] Take 200 mg of the cleaned cattail biomass obtained in step 1 and 300 mg of cobalt chloride and add them to 20 ml of ethanol solution. After ultrasonication for 5 min, heat and stir at 60 ° C for 30 min. After stirring, let the mixture stand for 1 h, take it out, and air-dry it in a fume hood for 24 h to obtain the Co adsorbed 2+ of biomass cattails.

[0043] Step 3: using chemical vapor deposition method, melamine is used as carbon source and adsorbed with Co 2+ The biomass cattails are calcined at high temperature in a nitrogen atmosphere to catalytically grow carbon nanotubes on the biomass-derived carbon microtubes, and finally a biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material with a hierarchical structure is obtained.

[0044] The melamine reagent and the Co adsorbed 2+ The containers of biomass cattails were placed in the horizontal tube furnace according to the front and rear positions, and the airflow direction was kept in the same direction as the melamine and Co adsorbed 2+ The front and back directions of the biomass cattail sticks are consistent. 2 The sample was calcined for 2 h at a heating rate of 5 °C / min to 800 °C in a molten-air atmosphere. After natural cooling, a biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material with a hierarchical structure was obtained, named Co-300.

[0045] Comparative Example 1

[0046] Step 1: Prepare biomass cattail sticks

[0047] An appropriate amount of cattail biomass sticks were washed with water and ethanol for several times, and the washed cattail sticks were placed in a 60° C. oven for continuous drying for 24 hours to obtain cleaned cattail biomass sticks.

[0048] Step 2: calcining the cleaned biomass cattails in a nitrogen atmosphere at a calcination temperature of 800° C. to prepare a biomass-derived carbon material named CMT.

[0049] Experimental Example 1: The microscopic morphology of the biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material prepared in Example 1 was observed using a scanning electron microscope.

[0050] Figure 2 This is a scanning electron microscope image of the biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material prepared in Example 1 of the present invention. As shown in the figure, the CNTs in Co-100 are attached to the surface of CMT. It can be clearly seen that the CNTs grow alternately on the surface of CMT, and their sizes are small and their morphologies are quite different.

[0051] Experimental Example 2: The structure of the biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material prepared in Example 1 was characterized using an X-ray diffractometer.

[0052] Figure 3 This is the XRD diagram of the biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material prepared in Example 1 of the present invention. As shown in the figure, the diffraction peak of Co-100 located at about 26.3° can be attributed to the graphitized carbon (002) crystal plane in the generated carbon nanotubes; the three obvious diffraction peaks near 44.2°, 51.5°, and 75.8° are metal cobalt. In the figure, the diffraction peak of the biomass-derived carbon material CMT is relatively weak, while the diffraction peaks of CNT and Co are very obvious, and the shape of the peaks tends to be sharp.

[0053] Experimental Example 3: The microscopic morphology of the biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material prepared in Example 2 was observed using a scanning electron microscope.

[0054] Figure 4 This is a scanning electron microscope image of the biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material prepared in Example 1 of the present invention. As shown in the figure, it can be clearly seen that the CNTs of Co-300 are aggregated on the surface of CMT, and clustering occurs.

[0055] Experimental Example 4: The structure of the biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material prepared in Example 2 was characterized using an X-ray diffractometer.

[0056] Figure 5This is the XRD pattern of the biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material prepared in Example 2 of the present invention. As shown in the figure, the diffraction peak of Co-300 located near 26.3° is attributed to the graphitized carbon (002) crystal plane in the generated carbon nanotubes; the three obvious diffraction peaks near 44.2°, 51.5°, and 75.8° are metallic cobalt, while the diffraction peak of biomass-derived carbon CMT is relatively weak.

[0057] Experimental Example 5: The microscopic morphology of the biomass-derived carbon material CMT prepared in Comparative Example 1 was observed using a scanning electron microscope.

[0058] Figure 6 This is a scanning electron microscope image of the biomass-derived carbon material CMT prepared in Comparative Example 1 of the present invention. As shown in the figure, the cattail biomass-derived carbon material CMT presents a one-dimensional hollow tubular structure.

[0059] Experimental Example 6: The structure of the biomass-derived carbon material CMT prepared in Comparative Example 1 was characterized using an X-ray diffractometer.

[0060] Figure 7 This is the XRD pattern of the biomass-derived carbon material CMT prepared in Comparative Example 1 of the present invention. As shown in the figure, a broad and weak large peak appears at 23.5°, indicating that CMT is a graphite material with an amorphous structure.

[0061] Experimental Example 7: The samples prepared in Examples 1-2 and Comparative Example 1 were uniformly mixed with paraffin wax (the filler loading of the samples was 10 wt%). The resulting mixture was compressed into a cylindrical test composite with an inner diameter of 3.04 mm, an outer diameter of 7.00 mm, and a thickness of 2.0 mm. The electromagnetic parameters of these samples were measured in the frequency range of 2.0–18.0 GHz using a vector network analyzer (VNA, AV3629D).

[0062] Figure 8-10 This is the electromagnetic loss diagram of the absorbing materials prepared by Examples 1-2 of the present invention and Comparative Example 1. As shown in the figure, the absorbing materials prepared by Examples 1-2 all have strong microwave absorption capabilities. The absorbing material prepared in Example 1 has an effective absorption bandwidth of up to 6.08 GHz at a thickness of 1.8 mm, and the corresponding strongest reflection loss value is -22.35 dB. The absorbing material prepared in Example 2 has an effective absorption bandwidth of 4.40 GHz at a thickness of 1.7 mm, and the corresponding strongest reflection loss value is -23.42 dB. The biomass-derived carbon material prepared in Comparative Example 1 has an effective absorption bandwidth of 3.92 GHz at a thickness of 1.5 mm, and the strongest loss value is only -12.71 dB. The above shows that the biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material can effectively improve the absorbing performance of the absorbing material.

[0063] Therefore, the present application provides a biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material, based on the unique hollow tubular hierarchical structure of the biomass-derived carbon material itself, using melamine as a carbon source and adsorbed Co 2+ The biomass cattails were calcined at high temperature in a nitrogen atmosphere, and carbon nanotube arrays coated with metal cobalt nanoparticles were catalytically grown on the biomass-derived carbon microtubes, and finally a composite material of carbon nanotubes @ carbon microtubes with a hierarchical structure was successfully obtained. It should be emphasized that the electromagnetic wave absorbing material Co-100 of the present invention has a wide effective absorption bandwidth of 6.08GHz (11.76-17.84GHz) and a maximum reflection loss of -22.35dB when the filler loading is 10wt% and the thickness is only 1.8mm, showing excellent lightweight and broadband wave absorbing characteristics. Including its advantages such as simple preparation process, low cost, and sustainable development, the present invention is superior to most existing microwave absorbing materials.

[0064] In the description of this specification, the description with reference to the terms "an experimental example", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the experimental example or example are included in at least one experimental example or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same experimental example or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more experimental examples or examples in a suitable manner.

[0065] Finally, it should be noted that the above experimental examples are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred experimental examples, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material, characterized in that: The preparation steps of the biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material are as follows: Step 1, washing the biomass cattail sticks with water and ethanol and then drying them in an oven to obtain washed biomass cattail sticks; Step 2: Add the cleaned biomass cattail and cobalt chloride into the ethanol solution to obtain the biomass cattail with Co adsorbed thereon. 2+ of biomass cattail sticks; Step 3: Using chemical vapor deposition, melamine is used as a carbon source and adsorbed with Co 2+ The biomass cattails are calcined at high temperature in a nitrogen atmosphere to catalytically grow carbon nanotubes on the biomass-derived carbon microtubes, and finally a biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material with a hierarchical structure is obtained.

2. The biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material according to claim 1, characterized in that: The specific steps of step 1 are: washing the biomass cattail sticks with water and ethanol for several times, and putting the washed cattail sticks into a 60° C. oven for continuous drying for 24 hours to obtain the cleaned biomass cattail sticks.

3. The biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material according to claim 1, characterized in that: The specific steps of step 2 are: adding the cleaned biomass cattail and cobalt chloride to the ethanol solution, ultrasonicating, heating and stirring; after the stirring, the mixture is allowed to stand, taken out, and air-dried in a fume hood to obtain the biomass cattail with Co adsorbed thereon. 2+ of biomass cattails.

4. The biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material according to claim 3, characterized in that: The specific steps of step 3 are: placing a container containing melamine reagent and a container containing Co adsorbed thereon 2+ The biomass cattail sticks were placed in a horizontal tube furnace and calcined for 2 hours under N2 atmosphere. After natural cooling, a biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material with a hierarchical structure was obtained.

5. The biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material according to claim 3, characterized in that: In step 2, the mass ratio of biomass cattail sticks to cobalt chloride is 2:1 or 2:3, the volume of the ethanol solution is 20 ml, the ultrasonic time is 5 min, the heating and stirring temperature is 60° C., the time is 30 min, the standing time is 1 h, and the air-drying time is 24 h.

6. The biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material according to claim 1, characterized in that: During calcination in step 3, the temperature is raised to 800° C. at a heating rate of 5° C. / min.

7. The biomass-derived carbon-based magnetic tubular composite electromagnetic wave absorbing material according to claim 1, characterized in that: The melamine reagent and the Co adsorbed 2+ When the container of biomass cattails is placed in the horizontal tube furnace, the direction of the airflow is kept in the same direction as the melamine and Co adsorbed 2+ The front and rear placement directions of the biomass cattail sticks are consistent.

Citation Information

Cited By

  • Wave-absorbing material and preparation method thereof

    CN120475696A